Near-Optimal Efficient MIMO Receiver for Miniature UAV-IoT Communications - Anas Saci; Arafat Al-Dweik; Shihab Jimaa (IEEE Open Journal of Vehicular Technology)
This article proposes a novel Direct Detection (DD) scheme for multiple-input multiple-output (MIMO) unmanned aerial vehicle (UAV) communications where tedious, slow, and computationally demanding channel state information (CSI) estimation and detection processes are not required. The proposed detection scheme is achieved by exploiting the frequency and/or temporal correlation among the transmitted signals to directly extract the information symbols from the received signals. The results obtained show that the proposed scheme offers a significant advantage of approximately 15 dB performance gain compared to conventional linear detection schemes, even when such schemes are using perfect CSI. Furthermore, the proposed detection algorithm can be efficiently implemented using the Viterbi Algorithm, or its variants, to achieve further complexity reduction.